Specialist cancer services for teenagers and young adults in England: BRIGHTLIGHT research programme - Rachel M Taylor; Lorna A Fern; Julie Barber; Faith Gibson; Sarah Lea; Nishma Patel; Stephen Morris; Javier Alvarez-Galvez; Richard Feltbower; Louise Hooker; Ana Martins; Dan Stark; et al. (NIHR Journals Library, 2021)
Background: When cancer occurs in teenagers and young adults, the impact is far beyond the physical disease and treatment burden. The effect on psychological, social, educational and other normal development can be profound. In addition, outcomes including improvements in survival and participation in clinical trials are poorer than in younger children and older adults with similar cancers. These unique circumstances have driven the development of care models specifically for teenagers and young adults with cancer, often focused on a dedicated purpose-designed patient environments supported by a multidisciplinary team with expertise in the needs of teenagers and young adults. In England, this is commissioned by NHS England and delivered through 13 principal treatment centres. There is a lack of evaluation that identifies the key components of specialist care for teenagers and young adults, and any improvement in outcomes and costs associated with it. Objective: To determine whether or not specialist services for teenagers and young adults with cancer add value. Design: A series of multiple-methods studies centred on a prospective longitudinal cohort of teenagers and young adults who were newly diagnosed with cancer. Settings: Multiple settings, including an international Delphi study of health-care professionals, qualitative observation in specialist services for teenagers and young adults, and NHS trusts. Participants: A total of 158 international teenage and young adult experts, 42 health-care professionals from across England, 1143 teenagers and young adults, and 518 caregivers. Main outcome measures: The main outcomes were specific to each project: key areas of competence for the Delphi survey; culture of teenagers and young adults care in the case study; and unmet needs from the caregiver survey. The primary outcome for the cohort participants was quality of life and the cost to the NHS and patients in the health economic evaluation. Data sources: Multiple sources were used, including responses from health-care professionals through a Delphi survey and face-to-face interviews, interview data from teenagers and young adults, the BRIGHTLIGHT survey to collect patient-reported data, patient-completed cost records, hospital clinical records, routinely collected NHS data and responses from primary caregivers. Results: Competencies associated with specialist care for teenagers and young adults were identified from a Delphi study. The key to developing a culture of teenage and young adult care was time and commitment. An exposure variable, the teenagers and young adults Cancer Specialism Scale, was derived, allowing categorisation of patients to three groups, which were defined by the time spent in a principal treatment centre: SOME (some care in a principal treatment centre for teenagers and young adults, and the rest of their care in either a children's or an adult cancer unit), ALL (all care in a principal treatment centre for teenagers and young adults) or NONE (no care in a principal treatment centre for teenagers and young adults). The cohort study showed that the NONE group was associated with superior quality of life, survival and health status from 6 months to 3 years after diagnosis. The ALL group was associated with faster rates of quality-of-life improvement from 6 months to 3 years after diagnosis. The SOME group was associated with poorer quality of life and slower improvement in quality of life over time. Economic analysis revealed that NHS costs and travel costs were similar between the NONE and ALL groups. The ALL group had greater out-of-pocket expenses, and the SOME group was associated with greater NHS costs and greater expense for patients. However, if caregivers had access to a principal treatment centre for teenagers and young adults (i.e. in the ALL or SOME groups), then they had fewer unmet support and information needs. Limitations: Our definition of exposure to specialist care using Hospital Episode Statistics-determined time spent in hospital was insufficient to capture the detail of episodes or account for the variation in specialist services. Quality of life was measured first at 6 months, but an earlier measure may have shown different baselines. Conclusions: We could not determine the added value of specialist cancer care for teenagers and young adults as defined using the teenage and young adult Cancer Specialism Scale and using quality of life as a primary end point. A group of patients (i.e. those defined as the SOME group) appeared to be less advantaged across a range of outcomes. There was variation in the extent to which principal treatment centres for teenagers and young adults were established, and the case study indicated that the culture of teenagers and young adults care required time to develop and embed. It will therefore be important to establish whether or not the evolution in services since 2012-14, when the cohort was recruited, improves quality of life and other patient-reported and clinical outcomes. Future work: A determination of whether or not the SOME group has similar or improved quality of life and other patient-reported and clinical outcomes in current teenage and young adult service delivery is essential if principal treatment centres for teenagers and young adults are being commissioned to provide 'joint care' models with other providers. Funding: This project was funded by the National Institute for Health Research (NIHR) Programme Grants for Applied Research programme and will be published in full in Programme Grants for Applied Research; Vol. 9, No. 12. See the NIHR Journals Library website for further project information.